Corporate Governance, Takeovers, and Top-Management Compensation: Theory and Evidence - Cyert, Richard M.; Kang, Sok-Hyon; Kumar, Praveen (Management Science, 2002)
We examine, both theoretically and empirically, top-management compensation in the presence of agency conflicts when shareholders have delegated governance responsibilities to a self-interested Board of Directors (BOD). We develop a theoretical framework that explicitly incorporates the BOD as a strategic player, models the negotiation process between the CEO and the BOD in designing CEO compensation, and considers the impact of potential takeovers by large shareholders monitoring the CEO-BOD negotiations. In equilibrium, internal governance by the BOD and external takeover threats by a large shareholder act as substitutes in imposing managerial control, especially in constraining management's profligacy in awarding equity-based compensation to itself. The model emphasizes factors in the design of compensation contracts that are rarely considered in the literature, such as equity ownership of the largest outside shareholder and the firm's bankruptcy risk. It also provides new perspectives on factors that are often considered in the literature, such as firm size, firm performance, equity ownership of the BOD, and BOD structure. Our empirical tests lend considerable support for our theoretical predictions. Equity ownership of the largest external shareholder, that of the BOD, and the default risk, are strongly negatively related to the size of CEO equity compensation. Consistent with the theoretical model, these factors do not significantly influence the growth of fixed (or non-performance-related) compensation. We also find that the equity ownership of the BOD is more important in managerial compensation control than other BOD related variables, such as BOD size or the proportion of outside directors.